2020
DOI: 10.4274/tpd.galenos.2019.6466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malaria Cases Detected in Antalya Province between 2012 and 2017

Abstract: Sıtma, Plasmodium cinsi parazitlerle enfekte olmuş Anopheles cinsi dişi sivrisinekler tarafından bulaştırılan önemli bir enfeksiyon hastalığıdır. Bu araştırmada, Antalya ilinde sıtma mücadelesine yönelik sürdürülecek çalışmalara katkı sunulması amaçlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The last indigenous case of malaria was detected in 2005 while in later years, cases with relapse and cases originating from abroad were detected due to increased travel related to tourism and commercial activities [64]. In another study conducted during 2012-2017 in Antalya Province, 36 malaria cases were detected, all of which were imported malaria cases from abroad [34]. The malarial parasite responsible for these infections was identified as P. falciparum (29 patients), P. vivax (4 patients), P. ovale (2 patients) and P. malariae (1 patient) ( Table 1).…”
Section: Epidemiology Of Malaria In Turkeymentioning
confidence: 99%
See 1 more Smart Citation
“…The last indigenous case of malaria was detected in 2005 while in later years, cases with relapse and cases originating from abroad were detected due to increased travel related to tourism and commercial activities [64]. In another study conducted during 2012-2017 in Antalya Province, 36 malaria cases were detected, all of which were imported malaria cases from abroad [34]. The malarial parasite responsible for these infections was identified as P. falciparum (29 patients), P. vivax (4 patients), P. ovale (2 patients) and P. malariae (1 patient) ( Table 1).…”
Section: Epidemiology Of Malaria In Turkeymentioning
confidence: 99%
“…The malarial parasite responsible for these infections was identified as P. falciparum (29 patients), P. vivax (4 patients), P. ovale (2 patients) and P. malariae (1 patient) ( Table 1). The author concluded that, for Turkey to remain malaria-free, early diagnosis and treatment of the disease and integrated mosquito control programs need to be uninterruptedly maintained [34].…”
Section: Epidemiology Of Malaria In Turkeymentioning
confidence: 99%